Autism Spectrum Disorder symptomatology in children with Mucopolysaccharide Disease Type III. (17th September 2018) - Wolfenden, Claire; Wittkowski, Anja; Jones, Simon A.; Rust, Stewart; Hare, Dougal J.
Accessible Summary: We now have a much better understanding of the specific characteristics of the many and often rare conditions that are associated with intellectual disabilities [learning disabilities] We examined a condition called Mucopolysaccharidosis Type III [MPS III] sometimes called Sanfilippo syndrome Many children with MPS III also appear to show signs of autism but an additional diagnosis of autism is time‐consuming and not always available to families We, therefore, measured autistic symptoms in children with MPS III and found that they often had problems in social responsiveness Children with MPS III and their families might therefore routinely benefit from the types of support offered to children with autism Abstract: Symptoms of autism spectrum disorder (ASD) are present in children with mucopolysaccharidosis type III (MPS III). Questionnaires measuring the two core domains of ASD (social responsiveness and repetitive behaviour) were completed by N = 17 parents of children with MPS III. Results indicated that scores consistent with ASD were reported by all parents on a measure of social responsiveness but lower scores were reported for repetitive behaviour. The findings provide support for the provision of additional interventions, focusing on social and communication difficulties, for children with MPS III across all phases of their disorder.